O museu como laboratório: Análise da exposição VI Jovem Arte Contemporânea - Heloisa Olivi Louzada (Midas: Museus e Estudos Interdisciplinares)
This article aims to discuss the exhibition VI Jovem Arte Contemporânea (Young Contemporary Art), which took place in 1972 at the Museu de Arte Contemporânea da Universidade de São Paulo (Brazil). The analysis considers the way in which the exhibition was conceived and organized, in the context of the museum as a laboratory, and also the wider political and social context, establishing comparisons with the exhibition Documenta, from the same year, and the debates organised by the International Council of Museums (ICOM). This discussion is based on documental resources, namely the texts written by artists and the museum’s directors who participated in the exhibition and in making the catalogue. The exhibition Young Contemporary Art was an important landmark among the exhibitions that took place in the Museum during the 1970s, generating discussions on the status of contemporary art and the importance of a laboratory-museum. Such discussions happened both in the Museum and at an international level, proposing a new way of thinking about the praxis of criticism inside the institutions that deal with modern and contemporary art.